AN ISSUE OF DEVELOPMENT STRATEGY FOR THE ROMANIAN ECONOMY IN THE EUROZONE CONTEXT - Cristina BĂLĂCEANU; Dorina MOCUȚA; Daniela PENU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper aims to identify the mechanisms by which the state and the entire economy will be geared towards identifying feasible solutions for creating a sustainable and lasting economy. This will require reforming the role of the state in the economy, depoliticizing actions and deeds that ensure the sustainability of the economy to eliminate corruptible actions and factors supporting corruption of the statistic system and those adjacent to them. Currently, the state economy is viewed piecemeal, based on the categories of economic agents who are being assisted or with whom they are developing partnership relations. The state also influences the social and economic conditions through the legal system, through promoted actions, generating systemic attitudes and behaviors at the entire societal community’s level. The state is directly involved in ensuring the welfare of society, if we look at this aspect through the prism of promoting factors of welfare, respectively endowment with factors of production, access to education, legal system that encourages the right to employment, infrastructure investments to accelerate the process of compatibility of the economies, with the auxiliary objective of creating alternative jobs but also moving to a higher stage of development in line with the principles of sustainable development.